Genetic diversity analysis for yield and yield contributing traits in mungbean (Vigna radiate L.): Genetic diversity analysis of mungbean (Bangladesh Journal of Agriculture, 2025)
An experiment was carried out at Sher-e-Bangla Agricultural University in Kharif-1 season with 33 genotypes of mungbean (Vigna radiate L.) to identify genetically diverse genotypes for yield contributing characters. The genotypes were evaluated for eight yield and yield contributing characters using a randomized complete block design with three replications. High heritability coupled with a high genetic gain was observed in days to 50% flowering, plant height, pod length, 100 seed weight, and seed yield per plant which indicated the effect of additive genes. Selection of these traits might cause the probability of simultaneous improvement of mungbean. The genotypes were grouped into four clusters based on the D2-value where cluster I was the largest and comprised of 13 genotypes followed by clusters III and IV with 6 genotypes in each. The highest inter-cluster distance was recorded between clusters II and IV (10.425) and the intra-cluster distance in cluster II (2.45). The lowest inter-cluster distance was found between clusters I and III (3.19). Principle component analysis revealed first four components contributed 88.77% towards genetic diversity in mungbean. Considering the magnitude of cluster means and agronomic performance the genotypes of cluster II and the genotypes of cluster IV might be suggested as parents for future hybridization programs.Bangladesh J. Agri. 2024, 49(2): 136-143